Distribution system and promotion of Makassar films - Puspitasari, Lilis; Bajari, Atwar; Hidayat, Dadang Rahmat; Cho, Sung Kyum (Universitas Padjadjaran, 2024)
Background: In the film industry, producers and distributors are responsible for producing quality films and ensuring they are effectively accessible to audiences. Therefore, the right distribution strategy is crucial to a film’s success in the market. Effective film distribution contributes to increased visibility of film works, revenue for producers and distributors, and awareness of film culture and stories. The same also applies to film production in Makassar. Local filmmakers often experience many obstacles in distributing films, ranging from limited budgets to the need for more screens due to a lack of audience enthusiasm. Therefore, marketing public relations is needed to reach the audience. Purpose: Therefore, analysing the barriers to distribution and promotion undertaken by filmmakers in Makassar is important to determine the proper distribution and promotion. Methods: This research uses qualitative research methods and uses a case study approach. Results: The research found that cinema remains the primary distribution channel for Makassar films despite limited screens and monopolistic practices. Filmmakers face challenges like unfavourable screening times and locations. Conclusion: Despite the rapid development of technology, cinema is still the most significant distribution and promotion dynamic. Even so, filmmakers can use alternative channels so that the right audience can consume films. In conducting the promotion, it is appropriate for Filmakker Makassar to use online media, offline media, and word of mouth. Through social media, promotion can reach a broader and faster audience; then, through offline media, such as roadshows, the filmmaker is able to attract support from various groups and local officials; the last is word of mouth. Community engagement can also attract potential audiences.